MiR-125 Family in Cardiovascular and Cerebrovascular Diseases - Wang, Yang; Tan, Jing; Wang, Lu; Pei, Gaiqin; Cheng, Hongxin; Zhang, Qing; Wang, Shiqi; He, Chengqi; Fu, Chenying; Wei, Quan (Frontiers in Cell and Developmental Biology, 2021)
Cardiovascular and cerebrovascular diseases are a serious threaten to the health of modern people. Understanding the mechanism of occurrence and development of cardiovascular and cerebrovascular diseases, as well as reasonable prevention and treatment of them, is a huge challenge that we are currently facing. The miR-125 family consists of hsa-miR-125a, hsa-miR-125b-1 and hsa-miR-125b-2. It is a kind of miRNA family that is highly conserved among different species. A large amount of literature shows that the lack of miR-125 can cause abnormal development of the cardiovascular system in the embryonic period. At the same time, the miR-125 family participates in the occurrence and development of a variety of cardiovascular and cerebrovascular diseases, including myocardial ischemia, atherosclerosis, ischemia-reperfusion injury, ischemic stroke, and heart failure directly or indirectly. In this article, we summarized the role of the miR-125 family in the development and maturation of cardiovascular system, the occurrence and development of cardiovascular and cerebrovascular diseases, and its important value in the current fiery stem cell therapy. In addition, we presented this in the form of table and diagrams. We also discussed the difficulties and challenges faced by the miR-125 family in clinical applications.